Primary culture and endocrine functional analysis of Leydig cells in ducks (Anas platyrhynchos) - Chu, Xiaoya; Javed, Aiman; Ashraf, Muhammad Faizan; Gao, Xiuge; Jiang, Shanxiang (Frontiers in Endocrinology, 2023)
Testicular Leydig cells (LCs) are the primary known source of testosterone, which is necessary for maintaining spermatogenesis and male fertility. However, the isolation, identification, and functional analysis of testosterone in duck LCs are still ambiguous. The aim of the present study was to establish a feasible method for isolating highly purified primary duck LCs. The highly purified primary duck LCs were isolated from the fresh testes of 2-month-old ducks via the digestion of collagenase IV and Percoll density gradient centrifugation; hematoxylin and eosin (H&E), immunohistochemistry (IHC) staining, ELISA, and radioimmunoassay were performed. Results revealed that the LCs were prominently noticeable in the testicular interstitium of 2-month-old ducks as compared to 6-month-old and 1-year-old ducks. Furthermore, IHC demonstrated that the cultured LCs occupied 90% area of the petri dish and highly expressed 3β-HSD 24 h after culture (hac) as compared to 48 and 72 hac. Additionally, ELISA and radioimmunoassay indicate that the testosterone level in cellular supernatant was highly expressed in 24 and 48 hac, whereas the testosterone level gradually decreased in 72 and 96 hac, indicating the primary duck LCs secrete testosterone at an early stage. Based on the above results, the present study has effectively developed a technique for isolating highly purified primary duck LCs and identified its biological function in synthesizing testosterone.